A Discoidal diorama as an examination of my quarter-life crisis - Meneses, Leticia Fortuna Francia
Upon turning thirty, I would come to realize that I'm going through what is called the "quarter-life crisis". Relatively new, this phenomenon had just been coined in the 90's by authors Abby Wilner and Alexandra Robbins. The quarter-life crisis describes shared experiences among people in their mid-twenties to late thirties. My quarter-life crisis realizations served as inspiration for my automated moving sculpture. The objective is to create a diorama to examine my quarter-life crisis; to analyze the phases of my life in a combined literal and metaphorical approach to produce a cohesive visual and personal narrative.